Development of a model for predicting the flash temperature during impact of titanium alloy. (July 2022) - Pan, He; Zhang, Yang
The use of light metals in mines is limited by the sparks and hot surfaces induced by mechanical friction and impact especially, hot surfaces which could ignite explosive atmospheres prior to the mechanical sparks. In view of this, the research on the collision hot surface is based on the simulation of the falling gravity hammer test. The change law of the collision temperature field with the impact conditions is obtained by numerical simulation. The mathematical model for calculating the maximum flash point temperature is derived. And proves that whether the flash temperature is related to the mass needs to consider the elastic-plastic deformation of the material itself. Only when the compressive stress reaches the extreme value or the material is ideal elastic-plastic material, the flash temperature is independent of the mass. In addition to the properties of materials, friction coefficient, relative velocity and normal load are the main factors affecting the compressive stress of impact. Thus, an important method can be obtained that controlling the coefficient of friction between the acting surfaces within a critical range by improving the processing accuracy of the material surfaces may ensure the safety of the hot surfaces generated by impact.